A ROLE OF PHYSICAL FACTORS AND COMPONENTS OF THE BIOPHYSICAL PHENOMENA IS IN PHYLLOGENETIC FORMING OF SPATIAL STRUCTURAL ORGANIZATION OF SINUSES OF HARD SHELL OF CEREBRUM - Cherno, V.S. (World of Medicine and Biology, 2010)
Multiple obtained data dealing with component organization of brain dura mater do not give whole idea of the origin, development, formation of the structures and their function. Research will require perfection, namely, the study of physical phactor influense on morphological peculiarities, their formation. Taking into account small number of reference data to use physical methods of research, we have proposed mathematical formulas of the movement of viscous substanse being not compressed. This has been done to study the factors whick influense structural space organization of fiber strutures of drain dura mater.